Antioxidant Effect of Epigallocatechin-3-Gallate in a Bleomycin-Induced Scleroderma Model - Ayse KOÇAK; Duygu HARMANCI; Zahide ÇAVDAR; Cemre URAL; Merih BİRLİK and Sülen SARIOĞLU and Osman YILMAZ and Gül GÜNER AKDOĞAN (Archives of Rheumatology, 2019)
Objectives: This study aims to evaluate the antioxidant effects of epigallocatechin-3-gallate (EGCG) in a bleomycin (BLM)-induced scleroderma model. Materials and methods: Thirty-two healthy female Balb-c mice (6-8-week-old; weighing 22±5 g) were used in this study. The mice were randomly divided into four groups: control (n=8), BLM (n=8), BLM+EGCG (n=8), and EGCG (n=8). Skin tissue specimens were collected at the end of the experiments. Histopathological examinations of skin tissues were performed. Skin samples were assessed for total superoxide dismutase activity and malondialdehyde content. The phosphorylation of p-38 mitogen-activated protein kinase and Akt protein (the serine-threonine protein kinase encoded by the AKT), as well as the nuclear factor-kappa B levels, were analyzed by western blotting. Results: Epigallocatechin-3-gallate-treated groups were observed to have reduced connective tissue fibrosis in the dermis area using Masson’s trichrome staining method. Pp-38 and nuclear factor-kappa B were found to decrease significantly in the BLM + EGCG group compared with the BLM group. Parallel to these findings, phosphorylated Akt protein was found to increase in the BLM + EGCG group compared with the BLM group. Superoxide dismutase activity was increased in the EGCG group and content of malondialdehyde level was decreased in EGCG groups. Conclusion: The results of the present study demonstrated that EGCG represses pp-38 and nuclear factor-kappa B signaling pathways, exerting a protective effect for scleroderma through its anti-oxidative role.